Students’ Attitude Towards Small Group Discussion In Reading Comprehension - Novita Kusumaning Tyas (Jurnal Ilmiah Pendidikan Scholastic, 2019)
In this globalization era, English becomes an important language that has to be mastered by all people around the world. There are four skills of English language; listening, speaking, reading, writing. All of the skills is important and integrated each other. Almost all activity in the classroom has relationship with reading. As stated in Sukirah Kustaryo (1998) “Reading is a process of making sense of written text through meaningful interpretation in relation to reader’s use of text and experimental/conceptual background for concept of written language, story structure, purpose and content of what is read”. Reading comprehension is a skill in reading. The reader cannot get information without comprehending the text. Desciptive research was applied in this research. The object of this study is 30 students from management informatics department who take English 1 class. Observation and surveys were used as data collection in this study. The result above showed that not all the students have a positive attiude towards discussion activity in reading comprehension. A small number of them, about 2.34%, have a negative attitude towards it. The intelligence affects their comprehension in reading a text. They comprehend the text easier than other.